Some Generalized Results on $G_{δ} $-diagonal Regular Spaces - Pralahad Mahagaonkar (International Journal of Mathematics And its Applications, 2015)
In this paper we constructed a space X possessing a regular $G_{δ}$-diagonal set of full measure, then the space X has a diagonal set if $\{(x,x):x\in X\} $ and is regular in $G_{δ}-set$ for $X× X$. We extend our result for some characterization of spaces with $G_{δ }$-diagonal set. Such a kind obtained by Borges.C.J.R [1], Cinder.J.G [2] and Zenor.P [5].